(untitled) (Research, Society and Development, 2022)
Objective: To trace the sociodemographic and professional profile of the subjects/nurses of the Primary Health Care network in the city of Recife - Pernambuco, considering the importance of this professional in health care in Primary Care. Methodology: Descriptive quantitative research. This is an excerpt from the field research of the master’s dissertation on the knowledge of primary care nurses about sexuality in climacteric. After approval by the Ethics Committee and Research with Human Beings of the University of Pernambuco, received on December 1, 2014, CAAE: 39337714.1.0000.5207, the letter of consent was issued by the City Hall of Recife so that the research could be started. Results: Of the 250 nurses interviewed, 90.3% are female, 45.3% of nurses were between 30 and 39 years old, 60% of these are married, 87% have one or two children and most are Catholics. As for the time of training in nursing, most have graduated for more than 10 years, and 72.5% graduated from a public university and only 3.7% do not have a graduate degree. The time of professional experience in the family health strategy of most nurses is more than 10 years (66.8%). Conclusion: It is essential to identify the profile of these professionals, in order to outline improvements in the performance of the activities carried out, to adopt measures that improve the care of the assisted population.